2019
DOI: 10.1016/j.apcata.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal oxide surface doping with phosphonic acid monolayers on alcohol dehydration activity and selectivity

Abstract: Controlling the near-surface environment of heterogeneous catalysts is of fundamental importance for high selectivity and activity. Self-assembled monolayers (SAMs) are effective tools to control reaction selectivity and activity for both supported noble metal and metal oxide catalysts. We previously demonstrated tunable dehydration activity of alcohols on phosphonic acidmodified, anatase-phase TiO2. In this work, we investigated the generality of this approach by studying the modification of other metal oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Reaction conditions appear to determine the selectivity: for example, Barteau and coworkers report near complete selectivity to dehydrogenation of isopropanol on anatase TiO 2 in continuous reaction studies using a packed bed reactor; 16 other researchers found only traces of dehydrogenation products in a vacuum temperature programmed desorption study; 19 still other reports indicate results that are intermediate between these latter extremes. 14,20 These conflicting reports may be due to some differences in reaction conditions (space velocity, conversion, temperature etc. ), yet based on these results it is not clear whether a TiO 2 catalysts would yield either dehydration or dehydrogenation products of a given alcohol in a reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction conditions appear to determine the selectivity: for example, Barteau and coworkers report near complete selectivity to dehydrogenation of isopropanol on anatase TiO 2 in continuous reaction studies using a packed bed reactor; 16 other researchers found only traces of dehydrogenation products in a vacuum temperature programmed desorption study; 19 still other reports indicate results that are intermediate between these latter extremes. 14,20 These conflicting reports may be due to some differences in reaction conditions (space velocity, conversion, temperature etc. ), yet based on these results it is not clear whether a TiO 2 catalysts would yield either dehydration or dehydrogenation products of a given alcohol in a reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphonic acids (PAs) are a promising alternative for the grafting of metal oxide surfaces, as discussed in various reviews [28][29][30] and by the study of PA-modified materials in a 4 variety of technological domains such as membrane separation 6,7,31 , supported metal catalysis [32][33][34]35 , hybrid (photo)electric devices 36 , implant materials 10,13 and chromatography. [37][38][39][40] In contrast to organosilanes, PAs are much less susceptible towards self-condensation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the dehydration rate was found to be strongly correlated to the dipole moment of the organophosphonic acid layers. A recent publication explored the behavior of other metal oxides under the same conditions 18 . Intriguingly, only materials that fell in a certain range of metal -oxygen bond strength, including TiO2 anatase, were positively affected by the presence of phosphonate SAMs.…”
Section: Introductionmentioning
confidence: 99%